Comparison of reproductive protection against bovine viral diarrhea virus provided by multivalent viral vaccines containing inactivated fractions of bovine viral diarrhea virus 1 and 2. Issue 26 (18th June 2018) - Walz, Paul H.; Riddell, Kay P.; Newcomer, Benjamin W.; Neill, John D.; Falkenberg, Shollie M.; Cortese, Victor S.; Scruggs, Daniel W.; Short, Thomas H.
Abstract: Bovine viral diarrhea virus (BVDV) is an important viral cause of reproductive disease, immune suppression and clinical disease in cattle. The objective of this study was to compare reproductive protection in cattle against the impacts of bovine viral diarrhea virus (BVDV) provided by three different multivalent vaccines containing inactivated BVDV. BVDV negative beef heifers and cows (n = 122) were randomly assigned to one of four groups. Groups A-C (n = 34/group) received two pre-breeding doses of one of three commercially available multivalent vaccines containing inactivated fractions of BVDV 1 and BVDV 2, and Group D (n = 20) served as negative control and received two doses of saline prior to breeding. Animals were bred, and following pregnancy diagnosis, 110 cattle [Group A (n = 31); Group B (n = 32); Group C (n = 31); Group D (n = 16)] were subjected to a 28-day exposure to cattle persistently infected (PI) with BVDV (1a, 1b and 2a). Of the 110 pregnancies, 6 pregnancies resulted in fetal resorption with no material for testing. From the resultant 104 pregnancies, BVDV transplacental infections were demonstrated in 73 pregnancies. The BVDV fetal infection rate (FI) was calculated at 13/30 (43%) for Group A cows, 27/29 (93%) for Group B cows, 18/30 (60%) for Group C cows, and 15/15 (100%) for Group D cows. Statistical differences were observed between groups with respect to post-vaccination antibody titers, presence and duration of viremia in pregnant cattle, and fetal infection rates in offspring from BVDV-exposed cows. Group A vaccination resulted in significant protection against BVDV infection as compared to all other groups based upon outcome measurements, while Group B vaccination did not differ in protection against BVDV infection from control Group D. Ability of inactivated BVDV vaccines to provide protection against BVDV fetal infection varies significantly among commercially available products; however, in this challenge model, the inactivated vaccines provided unacceptable levels of BVDV FI protection.